AGE-RELATED DIFFERENCES IN THE DEVELOPMENT OF MOTOR ABILITIES IN VOLLEYBALL - Petar Peev; Oleg Hristov; Anisa Nurja; Serafim Lazov; Petya Petkova; Milena Zdravcheva; Vera Antonova; Vlаdimir Kotev; Hristo Andonov (Scientific Publishing House. NSA Press, 2024)
There are a large number of publications related to conditioning in volleyball and in general. However, a very small part of them are related to the development of motor abilities in an age aspect. Such a study would be very difficult to implement, but at the same time, it would be beneficial in terms of the selection and sports orientation of youth volleyball. Volleyball as a sport has developed extremely dynamically in recent years, which makes it even more demanding in terms of fitness. The basic skills necessary for successful implementation in sports are complex and based on the athletes' ability to jump, sprint, and hit. From this point of view, the interest in this research was dictated, with the primary goal of determining the values of the main signs related to the volleyball game and compiling normative tables for control and assessment of preparedness. The research tasks also arise from the goal set in this way. To investigate the differences in the main essential characteristics of the volleyball game regarding age. To propose standards of control and evaluation. The methods we used to solve the problems are anthropometry, chronometry, tensiometry, speedometry, and mathematical-statistical methods (frequency, variation analysis, and sigma method). Results: The most significant increase in women was observed in the results of the jump tests and the speed of the serve (over 20 %) and smaller within 10% in the running tests. We attribute these results to the fact that the listed movements emphasize the training and competition process. Based on the obtained results, norms for evaluating the readiness of the contestants have been drawn up.